Foliar spraying with zinc oxide nanoparticles enhances the anti-osteoporotic efficacy of the fruit extracts of Silybum marianum L. by stimulating silybin production - Fahad Almulhim, Bedoor; Sherif, Fadia El; Younis, Nancy S.; Safwat, Yamen; Khattab, Salah (Frontiers in Plant Science, 2025)
IntroductionSilybum marianum is a medicinal plant that produces silymarin, which has been demonstrated to possess antiviral, anti-neurodegenerative, and anticancer activities. Silybin (A+B) are two major hepatoprotective flavonolignans produced predominantly in S. marianum fruits. Several attempts have been made to increase the synthesis of silymarin, or its primary components, silybin (A+B). Zinc oxide nanoparticles (ZnO-NPs) are considered a highly efficient Zn source widely used to promote crop development and productivity.MethodsIn this study, we aimed to investigate the effects of the foliar application of ZnO-NPs on the growth, yield, photosynthetic pigment content, silybin (A+B) content, and the expression of the chalcone synthase (CHS) gene in S. marianum plants. Different concentrations of ZnO-NPs were administered as foliar sprays to S. marianum plants growing in greenhouse conditions. Furthermore, we evaluated the anti-osteoporotic efficacy of the corresponding fruit extract against dexamethasone (Dex)-induced osteoporosis.Results and discussionFoliar treatment at all ZnO-NP concentrations increased the amounts of bioactive components of silybin (A+B), which enhanced the growth and yield of S. marianum plants while increasing the levels of N, P, K, and Zn in their leaves, roots, and fruits; the levels of photosynthetic pigments in their leaves; and silybin (A+B) content in their fruits, thereby increasing the medicinal value of S. marianum. The highest gains were observed in plants sprayed with the highest ZnO-NP concentration (20.0 mg/L). In addition, gene expression studies revealed that ZnO-NPs stimulated silybin (A+B) production by activating CHS genes. The administration of S. marianum extracts to Dex-administered rats increased osteoblast and bone formation while inhibiting osteoclast and bone resorption, thereby protecting the animals against Dex-induced osteoporosis.